Indonesia Sustainable Funding: Comparative of Standar Screening Securities Crowdfunding and Capital Markets - Kefi Miftachul Ulum; Maulida Khairunnisa; Rangga Suganda; Rodhotun Nimah; Fahmi Makraja (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2024)
Background: Since the occurrence of covid-19, there has been an acceleration in the transformation of the economic cycle with the digital era transforming conventional economic activities towards the digitization of the economy. This has given rise to financial technology as a concept, giving birth to securities crowdfunding instruments. This cycle has become an alternative for sustainable funding suitable for MSMEs, with funding reaching 1 trillion, supporting 481 business units and involving 160,368 investors. Data as of August 2023 shows funding for business units reaching 268 units, with a breakdown of 10 debt, 59 sukuk, and 199 equity fundings, with a comparative percentage of 78% conventional and 22% Sharia-compliant business units. The organization of this funding faces a legal vacuum in terms of standard screening for the issuance of business units being offered. The impact of this research aims to establish or strengthen regulations on standard screening for funding MSMEs in the securities crowdfunding cycle. Objectives: This research focuses on the standard screening and funding mechanisms of Securities crowdfunding and comparative with capital market. Novelty: In funding MSMEs and startup companies, there are no regulations regarding screening standards for sharia issuers/companies, so it needs to be compared with the screening standards used in the capital market. Research Methodology / Design: The legal problem of